Development of A Four-Tier E-Diagnostic Test on The Topic of Momentum to Measure and Reduce Student Misconception - Rusilowati, Ani; Darsono, Teguh; Sekarningtias, Felia Oktaviana; Fariyani, Qisti (Jurnal Pendidikan Fisika Indonesia, 2024)
This research aims to develop a set of e-diagnostic four-tier tests on Momentum topics that can be utilized to identify students' learning difficulties and misconceptions. The tests are to be valid, reliable, and effective. This research and development (R&D) project employed the 4-D model, which encompasses the following four stages: Define, Design, Develop, and Disseminate. The Define stage entailed a comprehensive needs analysis and identification of critical issues, while the Design stage encompassed the formulation of e-diagnostic four-tier test grids and instruments. The development stage comprised the implementation of development activities, expert validation, product testing, and the final assembly of the product. The dissemination stage involved the publication of the results of the development of the e-diagnostic four-tier test. The test was constructed in the form of a five-option multiple-choice test. Each question comprises four tiers or levels, ranging from questions, confidence levels, and reasons to the subsequent confidence level. The data collection instrument includes an assessment sheet for product validity, scoring guidelines, and a Likert scale for determining the practicality of product use. The data analysis technique employs the following formulas: (1) Aiken's V for testing validity, (2) Cronbach Alpha for determining reliability, (3) probability of answering correctly to ascertain the level of difficulty of the items, (4) differentiating power to determine the differentiating power, and (5) percentage to measure the level of misconception. The outcome of this research is a series of four-level diagnostic multiple-choice tests accompanied by explanatory material designed to address potential misconceptions. The tests have been evaluated rigorously for validity, item analysis, practicality, and effectiveness.